Pengaruh Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian Produk Pada PT. Tempo Scan Pasific Tbk. - Angelica Anastacia Ecklesia Terok; Hongky Dyrgo; Mercy Mantur (Journal of Mandalika Literature, 2025)
This study analyzes the influence of Brand Image and Product Quality on Purchase Decisions. The results indicate that the Brand Image (X1) and Product Quality (X2) variables have a positive but not significant influence on Purchase Decisions (Y) at PT. Tempo Scan Pacific, Tbk. The validity analysis shows that all variables have a correlation above the r-Table (0.273), with Cronbach's Alpha values greater than 0.70, indicating the reliability of the research instruments. Tests of normality, heteroscedasticity, multicollinearity, and autocorrelation assumptions were also met. However, the multiple linear regression test shows that the coefficient of determination (R²) is only 0.035, indicating a very small contribution from Brand Image and Product Quality to Purchase Decisions. Both variables have a positive but not significant influence on Purchase Decisions, both partially and simultaneously, as supported by the results of the T-test and F-test. Therefore, although these variables have a positive influence, their impact is not strong enough to significantly affect purchase decisions.action, which, in turn, will have a positive impact on the hospital.